Did Religion Help Me?: Coping During the COVID-19 Pandemic in Grenada - Herry, Arlette (Journal of religion and health, 2025)
The aim of this cross-sectional study was to investigate the relationship between religious (positive and negative) coping and coronavirus anxiety among churchgoers (N = 215) in Grenada during the height of the pandemic, and whether age, gender or religion predicted both phenomena. The Brief Religious Coping Scale (BCOPE) and coronavirus anxiety Scale (CAS) were used to measure religious coping and coronavirus anxiety, respectively. Pearson' correlation coefficient revealed a moderate, positive correlation between coronavirus anxiety and religious (positive and negative) coping, which was statistically significant (r = .463, p < .001; r = .569, p < .001). The regression analysis for predicting coronavirus anxiety found that both age (β = .386, p = < .001) and gender (β = .172, p = < .001 were statistically significant toward explaining the variance in coronavirus anxiety. Results also showed that age (β = −.456, p = < .001); β = −.326, p = < .001) has a statistically significant, negative association with both positive and negative religious coping. The importance of providing positive religious coping strategies for congregants and instrumental and emotional support, especially for females, is discussed.